2010
DOI: 10.1097/hjh.0b013e3283392673
|View full text |Cite
|
Sign up to set email alerts
|

Urinary angiotensinogen is correlated with blood pressure in men (Bogalusa Heart Study)

Abstract: Background-The Bogalusa Heart Study is a long-term study on cardiovascular disease and has followed a biracial (black/white) population from childhood. Risk factor data pertaining to many patients have been collected over 35 years, and the time course of hypertension has been documented by repeated examinations and measurements. Considerable sex and racial differences have been found to be related to cardiovascular disease. Urinary angiotensinogen (UAGT) is a novel biomarker for the intrarenal activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 76 publications
8
68
1
Order By: Relevance
“…By a positive feedback mechanism, Ang II increased AGT expression within the kidney, which subsequently led to additional increase of intratubular Ang II formation (18). In agreement with the concept that UAGT reflects intrarenal activation of the RAS, UAGT was found to correlate with high BP (20). Furthermore, inhibitors of the RAS are associated with reduced UAGT excretion (19).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…By a positive feedback mechanism, Ang II increased AGT expression within the kidney, which subsequently led to additional increase of intratubular Ang II formation (18). In agreement with the concept that UAGT reflects intrarenal activation of the RAS, UAGT was found to correlate with high BP (20). Furthermore, inhibitors of the RAS are associated with reduced UAGT excretion (19).…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, we found no significant effect of ALI on UAGT. Previous studies, however, showed a large variation of this measurement (19,20), and our study may have simply been underpowered to detect a significant effect of ALI on this parameter.…”
Section: Discussionmentioning
confidence: 66%
“…Many clinical studies also showed that urinary AGT level and prognosis might be correlated in patients with amyloidosis, DM, hypertension, renal transplantation, preeclampsia, IgAN, and chronic kidney disease (20,22,(32)(33)(34)(35)(36)(37)(38) A study on renal transplant patients with a mean proteinuria less than 1 g/day reported that basal urine AGT level was BP: Blood pressure, UP/Ucre: Urine protein-to-creatinine ratio, UAGT/Ucre: Urine angiotensinogen-to-creatinine ratio, LDL: Low-density lipoprotein, HDL: High-density lipoprotein, GFR: Glomerular filtration rate, CRP: C-reactive protein.…”
Section: Turk Neph Dial Transpl 2015; 24 (2): 195-201mentioning
confidence: 99%
“…Renin is produced by the cells of the juxtaglomerular apparatus cells and then delivered in the renal interstitium and vascular compartment resulting local generation of angiotensin. Angiotensin-converting enzyme is abundant in the kidney and is present in the proximal tubules, distal tubules, and collecting ducts (Kobori, 2010). Angiotensin I delivered to the kidney can also be converted to angiotensin II (Komlosi, 2003).…”
mentioning
confidence: 99%
“…All of the components necessary to generate intrarenal angiotensin II are present along the nephron (Navar, 2002;Kobori, 2007). Recently, in the Bogalusa Heart Study was proved that urinary level of angiotensinogen can be a new and potential marker of intrarenal RAS status in kidney disease due to arterial hypertension (Kobori, 2010). An important role in progression of inflammation and fibrosis seems to involve the renin-angiotensin system, and specifically the angiotensin-converting enzyme (ACE)-angiotensin (Ang) II-AT 1 receptor axis.…”
mentioning
confidence: 99%